(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The document examined here, drawn up by the Roman notary Ponziano de ’Ponziani, is presented in its formal characteristics as an instrumentum investimenti domus, a practice that perfected the state of ownership of a property, widespread almost everywhere in Italy and in particular in Rome The particular interest of this notarial deed is given by the very special circumstances in which it was drawn up (take possession of a house inhabited by plague-stricken Jews) and by other aspects pertaining to the serious situation determined by the plague epidemic that devastated Rome between May 1522 and June 1523